Efecto de la temperatura de hidratación de granos de arveja seca (lathyrus sativus) en los coeficientes de transferencia de masa - Flores Marceliano, Nancy Elizabeth (2019)
The main objective of this investigation was to determine the effect of the hydration temperature of dry pea grains (Lathyrus sativus) on the mass transfer coefficients. Therefore, in the research it was observed that temperature plays a fundamental role affecting the hydration process, to which 4 temperatures (25, 35, 45 and 55 ° C) were used, evaluating in 12 different times with its respective repetition and determining the kinetic parameters of the mass transfer models, it is deduced that Peleg and Page describe better the behavior of this grain. Likewise, the relationship between temperature and the kinetic parameters of mass transfer for hydration shows that the higher the temperature, the greater the weight gain and the less time required to reach equilibrium moisture. On the other hand, the Arrhenius equation helped to determine which is the best mathematical modeling.